(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
Edible plants from natural sources are receiving wide attention as a rich source of bioactive chemicals and an easily accessible resource that may contribute to the treatment of various diseases. Gonostegia hirta is an edible plant with folk claims used for wound healing, digestive aids and anti-inflammatory effects. In the present study, aerial parts of G. hirta, i.e. leaves and stem, were collected from three different geographical regions of India- Nagaland, Arunachal Pradesh and Uttarakhand. The morphological and anatomical characterisation of the plant was carried out by macroscopy, microscopy and powder drug analysis. The aerial parts were washed, pressed, shade-dried and pulverised, followed by preparation of the methanolic extract. The antibacterial activity of the methanolic extract was evaluated on five bacterial strains- Enterocococcus faecalis, Staphylococcus aureus (Gram-positive cocci), Salmonella sp., Pseudomonas aeruginosa, and Escherichia coli (Gram-negative bacilli) by micro-broth dilution assay. The size and shape, colour, surface, odour and taste, along with plant anatomy, including powder characters of plants collected from three different regions of India, were comparable with slight variations. Methanolic extracts of all regions showed antibacterial activity on a broad antibacterial spectrum, with a better effect on Gram-positive strains. Comparatively, this study validates the local practices of G. hirta preparation, suggesting that methanolic extracts could be effective for treating certain bacterial strains of clinical importance, in addition to being the first ever report of comparative geographical variations with respect to antibacterial activity.